Pengaruh Biaya Pemasaran, Omzet Penjualan terhadap Laba Perusahaan - Bakti Toni Endaryono; Prasetio Ariwibowo (LPPM Institut Nasional Laa Roiba Bogor, 2021)
This study aims to examine and analyze marketing costs and changes in sales turnover have a partial or simultaneous effect on company profits at a company. This research method uses quantitative methods with data collection methods through interviews and observations by processing company data. The data used are the financial statements of a company which are taken directly from the accounting department. The results of this study indicate that simultaneously and partially marketing costs and changes in sales turnover have a significant effect on company profits by 85.6% the remaining 14.4% are not included in this study.